A review: Towards practical attack taxonomy for industrial control systems - Qassim, Qais Saif; Jamil, Norziana; Jidin, Razali; Rusli, Mohd Ezanee; Zawawi, Md Nabil Ahmad; Jamaludin, Md Zaini; Z'aba, Muhammad Reza; Kamarulzaman, Wan Azlan Wan (Science Publishing Corporation, 2018)
Supervisory Control and Data Acquisition (SCADA) system is the underlying control system of most national critical infrastructures such as power, energy, water, transportation and telecommunication. In order to understand the potential threats to these infrastructures and the mechanisms to protect them, different types of cyber-attacks applicable to these infrastructures need to be identified. Therefore, there is a significant need to have a comprehensive understanding of various types of cyber-attacks and its classification associated with both Opera-tion Technology (OT) and Information Technology (IT). This paper presents a comprehensive review of existing cyber-attack taxonomies available in the literature and evaluates these taxonomies based on defined criteria.